The relationship between the performance of certain household bending activities and the age and physical limitations of sixty aged homemakers in Manhattan, Kansas - Warta, Marjorie Hamon (Kansas State University, 1961)
Americans are increasingly becoming more aware of the large increase in the proportion of the population who are over 65 years of age. It is expected that the number of Americans who are over 65 years of age will increase from 16 million to 20 million just 15 years from now. Although the husband may retire from industry, a homemaker never really "retires" but continues to be responsible for the household activities. This study investigated the extent to which age and physical limitations of aged homemakers affect their performance of household activities which require bending. An interview -schedule was used in gathering data during the month of June, 1960, from a randomly selected sample of 60 women between the ages of 70-79 living in 'Wards 3 and 4 of Manhattan, Kansas. For purposes of comparison the women were divided into age groups, the younger group 70-74, the older group 75-79 and according to the presence or absence of physical limitations. The interview -schedule contained questions to determine the extent of household activities requiring bending performed by aged homemakers and the changes made in the extent or method because of age and physical limitations. Nearly half of the 60 women lived alone in a household. Almost three fourths lived in a single family dwelling. About half of the 60 women lived in dwelling units of three or four rooms. Nearly one fourth of the women were responsible for the care of rooms other than those they occupied. Physical limitations were claimed by almost three fourths with arthritis being the most prevalent. Although the homemakers were in charge of the management of the household activities, half of them received some help, mostly from family members. The upkeep of the homes in which these women lived was rated subjectively by the interviewers as average or better for eight tenths of the homes. Vacuum cleaning was the method most widely used to care for floors, followed by wet mopping, hand cleaning and application of wax. The room most commonly vacuum cleaned was the living room, while the rooms most commonly wet mopped and hand cleaned were the kitchen and bathroom. None of the women had changed their method of vacuum cleaning floors, although nearly one third of those who wet mopped had changed their method of using a wet mop by using a different body position and/or different equipment. Half of the women did not presently hand clean floors, although 90 percent had hand cleaned floors at one time. Two thirds of the women waxed floors applying the wax by hand or using an applicator. The rooms most commonly waxed were the kitchen and bathroom. The cleaning of furniture and baseboards were done by nearly all women, with some doing little or no bending by using a handled dusting tool, by tilting the small furniture, or by using vacuum cleaner attachments. The bathroom fixtures were cleaned by nearly all of the women, although one fourth thought they did less now than at age 65. No bending was necessary for most when cleaning the bathtub or stool. Three fourths of the women thought they had problems when cleaning the bathroom fixtures, with cleaning the bathtub and lower outside stool being mentioned most frequently. It was hypothesized that age and the presence of physical limitations affect the household activities requiring bending which was done by these aged women. When the Chi Square test was applied, some significant differences were found for the physical limitations variable, but no significant differences were found for the age variable.
Keywords: House cleaning; Older people--Kansas--Manhattan